2019
DOI: 10.18632/aging.101990
|View full text |Cite
|
Sign up to set email alerts
|

CA-30, an oligosaccharide fraction derived from Liuwei Dihuang decoction, ameliorates cognitive deterioration via the intestinal microbiome in the senescence-accelerated mouse prone 8 strain

Abstract: Mounting evidence points to alterations in the gut microbiota-neuroendocrine immunomodulation (NIM) network that might drive Alzheimer’s Disease (AD) pathology. In previous studies, we found that Liuwei Dihuang decoction (LW) had beneficial effects on the cognitive impairments and gastrointestinal microbiota dysbiosis in an AD mouse model. In particular, CA-30 is an oligosaccharide fraction derived from LW. We sought to determine the effects of CA-30 on the composition and function of the intestinal microbiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 106 publications
(107 reference statements)
0
22
0
Order By: Relevance
“…As the most abundant microorganism being interdependent with human hosts, the gut microbiota not only constitutes a specialized microecosystem in gastrointestinal (GI) tract and harmonizes their relations dynamically, but is engaged in metabolic regulation and immune defense through the interplay with multiple distant organs and systems beyond the intestine 9 . In recent years, extensive studies have revealed that the microbiota–gut–brain axis is closely implicated in the pathophysiology of neurological diseases, which include but are not limited to Alzheimer’s disease 10 , autism spectrum disorder 11 , stroke 12 , 13 , multiple sclerosis 14 , and Parkinson’s disease 15 , 16 . As a crucial part of the axis, intestinal barrier dysfunction played an essential role in both gastrointestinal inflammatory diseases and neuropathology as well 17 .…”
Section: Introductionmentioning
confidence: 99%
“…As the most abundant microorganism being interdependent with human hosts, the gut microbiota not only constitutes a specialized microecosystem in gastrointestinal (GI) tract and harmonizes their relations dynamically, but is engaged in metabolic regulation and immune defense through the interplay with multiple distant organs and systems beyond the intestine 9 . In recent years, extensive studies have revealed that the microbiota–gut–brain axis is closely implicated in the pathophysiology of neurological diseases, which include but are not limited to Alzheimer’s disease 10 , autism spectrum disorder 11 , stroke 12 , 13 , multiple sclerosis 14 , and Parkinson’s disease 15 , 16 . As a crucial part of the axis, intestinal barrier dysfunction played an essential role in both gastrointestinal inflammatory diseases and neuropathology as well 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, a higher ratio of A. equolifaciens was found in the gut of patients with Alzheimer’s disease and autism spectrum disorder ( 46 , 47 ). In other studies, Roseburia hominis and Bacteroides_F pectinophilus were detected with a higher ratio in the patients with Alzheimer’s disease than that in healthy persons ( 48 , 49 ). When comparing the gut microbiome between the Parkinson’s disease group and normal group, we discovered Soleaferrea massiliensis more frequently in the patient group ( 50 ).…”
Section: Discussionmentioning
confidence: 67%
“…Preventive effects on Aβ-induced cognitive deficits were also observed in mice orally administered with Bifidobacterium breve A1 strain prior to the intracerebroventricular injection of Aβ 25-35 [135]. Likewise, other probiotics (e.g., SLAB51, VSL#3, ProBiotic-4), prebiotics (e.g., fructooligosaccharide, xylooligosaccharides, ferulic acid), synbiotics (e.g., a mixture of xylooligosaccharides and Lactobacillus paracasei HII01) and, even dietary and traditional medicine interventions (e.g., oligosaccharide fractions derived from Liuwei Dihuang decoction) are potentially neuroprotective in different models of aging as SAMP8 mice [136][137][138] and other murine age-linked models of the AD etiopathogenesis [139][140][141][142][143][144][145][146], alleviating the main age-related symptoms of the disease and delaying its progression. This fact seems to reflect deeper changes at biochemical level, i.e., a decreased microglial activation, inflammation, oxidative stress and Aβ accumulation, increased levels of hippocampal BDNF and of genes involved in synapse processes [40,145,146].…”
Section: Admentioning
confidence: 99%